ATAP DESALINASI SEBAGAI SOLUSI PEMENUHAN KEBUTUHAN AIR BERSIH DI DAERAH PESISIR - Astuti, Ulvi Pri (Universitas Nahdlatul Ulama Sidoarjo, 2016)
Seawater or brackish water processing technology to freshwater was known as desalination. Process desalination of evaporation is one of the desalination technique, that effective and economics especially to a coastal area that have larger sun intensity than another. Therefore, in this research will discuss about designing house roof society in coastal region. Tub evaporative and basic tub plate planning size that made for 4,5m x 10m house of floordeck 600 coated with 5,4 cm concrete thick mess. Tub evaporative size is 3m × 10m × 0,02m. Collective freshwater channel are besides the tub with size 0,75m × 10m. The sketch of roof used easel that made of galvalume profile C 100mm × 50mm × 20mm × 4mm and gording is made of hollow 40mm × 40mm × 0,5mm. Outside cover roof is polytron polycarbonate with 4,2 mm thickness and inside roof fiberglass with 1 mm thickness. Freshwater volume can be produced by tub space 3m × 10m × 0,003m is 89,74 L by seven hours heating process on 485 W/m2 sun intensity.